Management of a mandibular molar with C-shape root canal using spiral computed tomography as a diagnostic aid - Niharika Jain; Kabbur Thippanna Chandrashekar; Abhishek Gupta; Permanand G Makhija (Journal of International Clinical Dental Research Organization, 2014)
The aim of this article is to present the use of spiral computed tomography (CT) in endodontic management of a mandibular molar with an unusual morphology of C-shape canal. An accurate assessment of this unusual morphology was made with the help of spiral CT. This report extends the range of known possible anatomical variations to include teeth with an abnormal number of roots and canals. This report also highlights the role of spiral CT, over conventional intra-oral periapical radiographs, as an objective method to confirm the three-dimensional anatomy of teeth.